The modern state of learning outcomes assessment (the case of geologist education) - Marianna Kuzko (Університети і лідерство, 2020)
Assessment is an important element of educational process. It evaluates the level of student preparation as well as influences its quality. The article focuses on methods of learning outcomes’ assessment. It is based on the results of the future geologists` curricula and syllabus analysis, observation of educational process, and the survey conducted among future geologists. The study shows the imperfection of the current summative assessment of future geologists and reveals the main reasons for competencies assessment` inefficiency. The list of the most common task types that are usually being used by educators for the learning outcomes assessment of future geologists is composed; and frequency rate of their use and the students’ attitude towards them is identified. Some explanations about students` bias toward the most popular (among educators) assessment methods are provided. The article proposes an assessment procedure suitable for vocational training of future geologists, starting from the assessment methods selection and up to educator`s feedback.